The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000479405
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exogenous Hydrogen Sulfide in Free Fatty Acids Induced Inflammation in Macrophages

Abstract: Background: This study aimed to investigate whether exogenous hydrogen sulfide (H2S) can protect the RAW264.7 macrophages against the inflammation induced by free fatty acids (FFA) by blunting NLRP3 inflammasome activation via a specific TLR4/NF-κB pathway. Methods: RAW264.7 macrophages were exposed to increasing concentrations of FFA for up to 3 days to induce FFA-induced inflammation. The cells were pretreated with NaHS (a donor of H2S) before exposure to FFA. Cell viability, cell apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Original magnifcation, 200 × . [32][33][34]. Here, this study provides the first evidence of exogenous NaHS observably suppressed the expression of NLRP3 inflammasome in PA-induced HepG2 cells.…”
Section: Discussionsupporting
confidence: 53%
“…Original magnifcation, 200 × . [32][33][34]. Here, this study provides the first evidence of exogenous NaHS observably suppressed the expression of NLRP3 inflammasome in PA-induced HepG2 cells.…”
Section: Discussionsupporting
confidence: 53%
“…H 2 S, previously regarded primarily as an environmental hazard and toxic gas, has recently been recognized as the third gasotransmitter after carbon monoxide (CO) and nitric oxide (NO; Szabo, ). H 2 S has become a focus of researches because of its role in various biological processes, such as neuronal health (Paul & Snyder, ), cardiovascular health, immune response (Yuan, Shen, & Kevil, ), and inflammation (Luo et al, ). Besides, H 2 S has also been reported to regulate cell cycle, proliferation, autophagy, apoptosis, and oxidative stress in malignant tumors (Hellmich & Szabo, ).…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB plays a critical role in regulating inflammation and serves as the first signal in the activation of the NLRP3 inflammasome. 12 , 39 41 Previous studies demonstrated that NF-κB inhibition led to a remarkable reduction of NLRP3 expression. 33 We found that blocking NF-κB activation with the NF-κB inhibitor BAY-117082 could downregulate NLRP3 expression in BGC-823 cells.…”
Section: Discussionmentioning
confidence: 99%